Photograph of the Mural of cannery workers in the 1930s. - Steven Domingo:::Photographer::::::::::::; Vinnie Lopez:::Photographer:::::::::::: (Monterey, California, 2023)
Photograph of the mural titled 'cannery workers in the 1030s,' by the artist John Cerney, found on a wall by the Monterey Bay Coastal Trail in Monterey, California. John Cerney is a Monterey County based artist. He has painted hundreds of murals on display all around the country.